(untitled) (Islamic Sciences Journal, 2023)
The science of doctrine is divided among the scholars of theology into three sections of the divinities section, which deals with the existence of Allah, its oneness and attributes. The section of prophecies, it deals with the general prophecy of all prophets and their rulings and the prophecy of the Messenger (Peace be Upon Him).The third section is audiology and includes paradise, fire, attitude, path, balance, and arithmetic , Presentation and all unseen judgments mentioned in it are proven by the Qur’an and Sunnah, and Paradise is one of these dogmatic audios that a true Muslim is required to believe in and in their fixed descriptions in the Holy Quran and Sunnah.